Intelligence Adverse Resilience in Improving the Quality of Decision-Making of Madrasah Foundation Chairmans in East Java Province - Supriadi; Samsu; M. Syahran Jaelani (Maneggio, 2026)
This study aims to describe the level of adversity quotient, analyze the quality of decision-making, identify the role of adversity quotient in strategic decision-making processes, and examine the relationship between the two among Islamic foundation (madrasah foundation) leaders in East Java Province. Employing a phenomenological qualitative approach, the research was conducted at three foundations representing different regional contexts: Amanatul Ummah Mojokerto Foundation (semi-urban Islamic boarding school-based), Al-Huda Kediri City Foundation (competitive urban), and Darul Madinah Gresik Foundation (industrial-coastal area). Data were collected through semi-structured interviews, participatory observation, and documentation, then analyzed using Miles and Huberman's interactive model. The results reveal three main findings. First, foundation leaders with high adversity quotient demonstrate more adaptive and strategic decision-making patterns. Second, differences in socio-cultural and geographical contexts influence leadership character: Amanatul Ummah Foundation exhibits a strategic-hierarchical Climber-type pattern, Al-Huda Foundation displays a directive-authoritative pattern, and Darul Madinah Foundation reflects a pragmatic-responsive pattern. Third, the integration of local values ​​sumeleh and seeks to strengthen the control and endurance dimensions within Stoltz's CORE framework. This study concludes that a high level of adversity quotient, combined with emotional intelligence and contextual awareness, contributes significantly to effective, efficient, and sustainable decision-making quality for madrasa development.